On the privacy protection of fingerprint templates - Li, Sheng. (2013)
Nowadays, biometrics is widely used in authentication systems. In general, biometrics needs to be stored in a database for subsequent authentication. However, templates stored in the database are at the risk of being stolen or modified. Once the template is stolen, it is difficult to be replaced like passwords and the private personal information associated with the stolen template would also be exposed. Thus, biometric templates have to be stored in the database so that both the privacy of the template and the security of the system are not compromised under various attacks.